Determination of safety distances due to the seismic earthquakes during blasting at the Open Pit North Mining District of the Majdanpek copper mine - Rajković Radmilo; Gomilanović Miljan; Kržanović Daniel; Stepanović Saša; Mikić Miomir; Jovanović Milenko (Mining and Metallurgy Engineering Bor)
Majdanpek is located right next to the mine, so blasting at the Open Pit North Mining District could have an impact on the environment. If the intensity of that impact exceeds the prescribed limits, the harmful and dangerous consequences could be for people and facilities. In order to protect the environment from the harmful effects of blasting, the standards for protection and limits for the intensity of manifestation the certain effects of blasting at a certain distance are prescribed. This paper shows the determination of safety distances during blasting due to the seismic waves.